Mayor Crump Don't Like It : Machine Politics in Memphis - Dowdy, G. Wayne (Book collections on Project MUSE., 2006)
In the 1930s thousands of African Americans abandoned their long-standing allegiance to the party of Abraham Lincoln and began voting for Democratic Party candidates. This new voting pattern remapped the nation's political landscape and altered the relationship between citizen and government. One of the forgotten builders of this modern Democratic Party was Memphis mayor and congressman Edward Hull Crump (1874-1954). Crump created a biracial, multiethnic coalition within the segregated South that transformed the Mississippi Delta's largest city into a modern southern metropolis. Crump expand.